Bee colony optimised mass rapid transit routing prototype - Wang, Chen; Wood, Lincoln C.; Lim, Arthur Davis; Abdul-Rahman, Hamzah (ICE Publishing, 2017)
Mobility is an essential aspect for tourists visiting large cities; thus, an effective and efficient route guide for tourists to move in, around and out of the cities is needed. This research aims to develop an light rail transit (LRT)/mass rapid transit (MRT) routing prototype by applying the bee colony optimisation (BCO) and to pilot run this system to determine its functionality and workability. Through a questionnaire survey conducted among 900 LRT/MRT users in Klang Valley and data analysed using the BCO algorithm, a BCO-LRT/MRT routing prototype for Klang Valley was developed to assist tourists, especially those who are spending shopping vacations but unfamiliar with this region. With the assistance of this prototype, travellers can optimise the vacation schedule even in a very limited duration. The route determined by this prototype consumes much shorter duration than the one that the LRT/MRT users preferred. It can establish a route covering more than one destination. This prototype did not yet cover business centres, scenic spots and hotels; thus, a huge potential for the BCO-LRT-MRT prototype to upgrade is expected in a future study.